Geospatial techniques for assessment of bank erosion and accretion in the Marala Alexandria Reach of the River Chenab, Pakistan - Ch, M. Hamid; Ashraf, M.; Hamid, Qudsia; Sarwar, Syed Mansoor; Saqib, Zulfiqar Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2017)
Remote Sensing (RS) and Geographical Information Systems (GIS) are widely used for change detection in rivers caused by erosion and accretion. Digital image processing techniques and GIS analysis capabilities are used for detecting temporal variations of erosion and accretion characteristics between the years 1999 and 2011 in a 40 km long Marala Alexandria reach of River Chenab. Landsat satellite images for the years 1999, 2007 and 2011 were processed to analyze the river channel migration, changes in the river width and the rate of erosion and accretion. Analyses showed that the right bank was under erosion in both time spans, however high rate of deposition is exhibited in middle reaches. The maximum erosion was 1569843 m2 and 1486160 m2 along the right bank at a distance of 24-28 km downstream of the Marala barrage in the time span of 1999-2007 and 2007-2011, respectively. Along right bank mainly there is trend of accretion but erosion is much greater between 20 and 28 km reach. Maximum accretion was 5144584 m2 from 1999-2007 and 2950110 m2 from 2007-2011 on the right bank downstream of the Marala Barrage. The derived results of channel migration were validated by comparing with SRTM data to assess the accuracy of image classification. Integration of remote sensing data with GIS is efficient and economical technique to assess land losses and channel changes in large rivers.